Lessons learned from the development and implementation of a patient-reported outcome and experience measure (POEM) in an Australian glaucoma practice - Fraenkel, Alison; Lee, Graham A.; Vincent, Stephen J; Vincent, Roslyn A.; Bourne, Rupert R. A.; Shah, Peter (BMC ophthalmology, 2019)
Background A patient’s perception of how their glaucoma is managed will influence both adherence to their medication and outcome measures such as quality of life. Methods Prospective consecutive study using a Glaucoma Patient-reported Outcome and Experience Measure (POEM) modified for an Australian ophthalmic private clinical practice setting. The Australian Glaucoma POEM consists of eight items related to the patient’s understanding of the diagnosis and management, acceptability of the treatment, whether they feel their glaucoma is getting worse, interfering with their daily life and concerns regarding loss of vision as well as addressing whether they feel safe under the care of their glaucoma team and how well their care is organised. Results Two hundred and two patients (M:F 91:111) participated in the study. Mean ± standard deviation for subject age was 69 ± 13 years. Patient’s overall perception of their treatment and outcome was favourable. Younger patients felt their glaucoma interfered more with their daily lives and were more worried about losing vision from glaucoma. The greater the number of medications in use, the more they felt their glaucoma was getting worse and that glaucoma interfered with their daily lives. With all other variables accounted for by the multivariate linear model, female patients more strongly agreed that they understood their glaucoma diagnosis and glaucoma management. The patients with a severe visual defect in their worse eye, reported a greater perceived understanding of their glaucoma diagnosis and management and that they felt that glaucoma had a greater interference on their daily life. They were also more concerned about losing vision from glaucoma than their fellow glaucoma patients with less severe or no visual field deficit in the worse eye. Conclusions The modified POEM demonstrates potential to capture the concerns of a practice’s glaucoma cohort with a view to enhancing the quality of glaucoma care delivered.